The Sounds of English Theory and Practice for Latin American Speakers - José Vicente Abad Olaya (2020)
do you speak English? Most people ask this question when they want to know whether you can communicate in this language. By doing it they evince the widespread tendency to equate our ability to speak with our overall communicative competence. Paradoxically, for most EFL and ESL learners, speaking is the most challenging skill and the last they get to develop to the full. Latin American students' reluctance to speak English often comes down to their fear of mispronouncing it. They soon learn that the pronunciation of English does not correspond with its spelling. However, most students ignore that a significant number of English sounds are not present in Spanish, and that they must be learned in order to pronounce English properly. The main objective in writing this book is to help Latin American students of English, particularly novice and practicing English teachers, not only to hone their pronunciation but also to acquire the technical elements necessary to teach it. To that aim this book provides readers with essential theory and practice on the pronunciation of English sounds and contrasts them with those of Spanish. Although originally intended for classroom use, this book can also be used for self-study by learners with an English proficiency level of B1 (intermediate) or above.